Effect of Technological Interventions on Yield and Economics of Pigeon pea in Eastern U.P. - A.P. Dwivedi, R.P.Singh, Mamta Singh (Indian Journal of Extension Education, 2022)
Pigeon pea is an important pulse crop widely consumed in India. It is also play an important role in sustainable agriculture enriching the soil through biological nitrogen fixation The area, production and productivity of the pulses in the country are 23.63 million hectare, 14.56 million tones and 6.25 q/ha, respectively. Looking of fact its yield productivity is far below the potential yield. Krishi Vigyan Kendra, Post Graduate College, Ghazipur conducted front line demonstration on the improved package of practices of pigeon pea in the district during 2005-06 to 2009-10 for five consecutive years. The highest grain yield (20.0 q/ha) was recorded in the year 2007-08. In front line demonstration, it was 42 per cent more over the farmers practice (14.0 q/ha), however the lowest yield (7.0 q/ha) was recorded in the year 2006-07 under FLD and 6.0 q/ha in farmers practice. The variation in the percent increase in the yield was found due to variation in agro climatic parameters under rain fed condition. The productivity and income gain under FLDs over traditional practices of pigeon pea cultivation created greater awareness and motivated the other farmers to adopt appropriate production technology of pigeon pea in the district. The selection of critical input and participatory approach in planning and conducting the demonstration definitely help in transfer of technology to the farmers.